The Scientific American science desk reference (New York John Wiley, 1999)
"Divided into 15 sections covering a specific scientific discipline, this work includes sections on key concepts, glossaries, and biographies of prominent researchers in that field, chronologies, and information unique to that particular discipline."--"Outstanding Reference Sources," American Libraries, May 2001
Includes bibliographical references and index
Also available as an electronic book via the World Wide Web to institutions affiliated with netLibrary, Inc
1
Keywords: Science -- Handbooks, manuals, etc; Science -- Miscellanea